Optimal location of battery swap stations for electric vehicles - Gallego Rendón, Ramón Alfonso; Hincapié Isaza, Ricardo Alberto; Osorio Cruz, Fabio Andrés (Scientia et Technica, 2019)
In this paper, a methodology that allows to determine the location and optimal sizing of battery swap stations for electric vehicles in distribution networks is proposed, which objective is to minimize investment costs and technical losses of the network. The set of constraints is associated with technical and operational characteristics of the system. To solve the mathematical model, an evolutionary algorithm is used. To verify the efficiency of the methodology, a Colombian distribution system is used, where the obtained results validate what is proposed in this work.